Properties of Concrete Columns Strengthened by CFRP-UHPC under Axial Compression - Bo Wang; Gejia Liu; Jiayu Zhou (Buildings, 2023)
Ultra-high-performance concrete (UHPC) is a kind of structural material with ultra-high strength, extremely low porosity, and excellent durability, which has extremely broad application prospects. In order to promote the application of UHPC constrained by carbon fiber-reinforced polymer (CFRP) sheets as strengthening material in practical engineering, a total of nine specimens were designed, and two kinds of UHPC strengthening layer thickness (35 mm and 45 mm, respectively) were designed. By changing the constraint form of the UHPC strengthening layer (longitudinal reinforcements and ordinary stirrups, longitudinal reinforcements and spiral stirrups, and CFRP sheets, respectively), the axial compression performance of the strengthened column was explored. The study shows that compared with the without strengthened column, the uplift of carrying capacity of the strengthened test column is 277–561%. The reinforcement form of the strengthening layer has little influence on the lifting capacity. Among the three different strengthening methods, the wrapped CFRP has the best improvement effect on carrying capacity and ductility, followed by longitudinal reinforcements and spiral stirrups in the strengthening layer. With the increase of CFRP layers from two to five layers, the maximum carrying capacity increases by 21.3%. The carrying capacity of three different types of UHPC-strengthened columns is theoretically calculated, and the accuracy of the theoretical calculation method is verified by comparing the test value with the theoretical value, which provides a theoretical basis for the application of UHPC-strengthened columns in the future.